2021
DOI: 10.1021/acs.orglett.1c03497
|View full text |Cite
|
Sign up to set email alerts
|

Studies toward the Total Syntheses of Calyciphylline D-Type Daphniphyllum Alkaloids

Abstract: An efficient construction of an aza-[5.7.6.5] tetracyclic core structure of calyciphylline D-type Daphniphyllum alkaloids has been achieved. The synthetic route features a diastereoselective cyclopropanation, efficient construction of the core bridged 8-aza-[3.2.1]­octane skeleton through a [3 + 2] IMCC strategy, oxidative dearomatization of phenol, and gram-scale preparation in each step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We began this project by studying the Lewis acid‐induced reaction of the indole‐derived DA cyclopropane 1 [15] with primary amines 2 affording tropane derivatives peri ‐annulated to the indole ring 3 (Scheme 1c). It was earlier shown that aldehydes react with amines faster than DA cyclopropanes, [14b,16] this allows the goal process to be realised as a domino reaction. Our choice of substrates was motivated by their availability and the assumption that the resulting products 3 should have important physiological activities.…”
Section: Introductionmentioning
confidence: 99%
“…We began this project by studying the Lewis acid‐induced reaction of the indole‐derived DA cyclopropane 1 [15] with primary amines 2 affording tropane derivatives peri ‐annulated to the indole ring 3 (Scheme 1c). It was earlier shown that aldehydes react with amines faster than DA cyclopropanes, [14b,16] this allows the goal process to be realised as a domino reaction. Our choice of substrates was motivated by their availability and the assumption that the resulting products 3 should have important physiological activities.…”
Section: Introductionmentioning
confidence: 99%
“… 17 With this strategy, the fused 5–7 bicycle was efficiently constructed which matched the trans -stereochemisty, however a C-4 oxygen atom was not be direct. Following our previously developed [3 + 2] IMCC strategy, 18 a – h we have recently reported a novel and efficient construction of a bridged aza-[3.2.1]octane-embedded 5–7–6 tricyclic carbon skeleton with desirable substituents and stereochemistries toward total syntheses of calyciphylline D-type Daphniphyllum alkaloids ( Scheme 3 ). 18 i Herein, we report the application of the [3 + 2] IMCC strategy for efficient construction of the bridged oxa-[3.2.1]octane-embedded 5–7–6 tricycle with stereochemistries on C-4, C-7 and C-10, as well as a methylene (methyl) group at C-6 matching those in neoglabrescin A, curcusones I/J and related rhamnofolane/tigliane/daphnane diterpenes.…”
mentioning
confidence: 99%
“…Due to their broad moderated biological activities as well as their unprecedented structures, the total synthesis of Daphniphyllum alkaloids came into focus in the 1980s when Heathcock and co-workers accomplished a landmark synthesis of six members in four subtypes by biomimetic synthesis . After that, a series of elegant total syntheses and constructive studies on the skeleton of Daphniphyllum alkaloids constantly updated our understanding of these molecules . Kobayashi and co-workers successfully reported the isolation of five novel hexacyclic daphniphyllum alkaloids: Daphmanidin A ( 1 ), E ( 3 ), and F ( 4 ), Daphtenidine C ( 5 ), and Calyciphylline N ( 2 ) from 2002 to 2009, composing as a new subtype of Daphmanidin A-type (Figure ).…”
mentioning
confidence: 99%